Survey of impact glasses in shergottites searching for Martian sulfate using X-ray absorption near-edge structure. (15th November 2021) - Shidare, Masashi; Nakada, Ryoichi; Usui, Tomohiro; Tobita, Minato; Shimizu, Kenji; Takahashi, Yoshio; Yokoyama, Tetsuya
Abstract: The surface of Mars has experienced progressive oxidation, resulting in the formation of sulfate minerals as evidenced from surface exploration missions. However, no clear evidence for the presence of sulfate minerals has been reported within Martian meteorites. This study examined sulfur speciation in impact glasses of three basaltic shergottites, Elephant Moraine (EETA) 79001, Larkman Nunatak (LAR) 06319, and Dhofar 019, using X-ray absorption near-edge structure (XANES) spectroscopy. The measured XANES spectra were classified into four types: (1) sulfide, (2) highly reduced sulfide glass (∼IW+1), (3) mixture of sulfide and sulfate, and (4) sulfate. The sulfate spectra observed from EETA79001 and LAR 06319 were mixed with sulfide from the reduced igneous host rock as impact glasses were formed by shock on the surface of Mars, both sulfide and sulfate would have possibly originated on Mars. Besides, highly reduced sulfide present in the same impact glasses is inconsistent with secondary alteration on the oxic Earth's environment. In contrast to EETA79001 and LAR 06319, all of the XANES spectra from Dhofar 019 showed the only sulfate, whose origin is most likely from terrestrial alteration. Combining with the geochemical signatures of volatile elements (e.g., D/H, C, and halogens) in impact glasses of EETA79001 and LAR 06319, we propose two possible scenarios for the formation of sulfate species to the shergottite host-rocks: (i) oxidation of sulfide minerals by subsurface oxic water in Mars, or (ii) precipitation of sulfate mineral derived from Martian subsurface water. The difference between the two models is the source of S(VI) species, whether it originated from (i) magmatic sulfide in shergottite or (ii) sulfate ion in the subsurface water/ice. Both models indicate that the ancient (∼4 Ga) water reservoir might have already been oxic, and it requires post-magmatic water–rock interaction that formed sulfate minerals whose oxidized signatures were incorporated into impact glass.